Silêncio, sensações e segredos: o narrador e a personagem feminina no romance O lustre (1946), de Clarice Lispector - Santos Júnior, Moisés Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This project has as its main purpose to analyze Clarice Lispector's second novel, O lustre, published in 1946 and currently considered by literary criticism one of her minor works. The study analyze mainly the development of the narrator and the main character Virginia, as the most expressive categories in the novel, as well as categories of disruption. The research has also the purpose of highlighting the avant-garde and modern aesthetics, especially of Impressionism, which reverberate in Lispector's writing this book. The whole investigation has the purpose of establishing O lustre as a work of great aesthetic and literary quality, demystifying the critical position which defends the little relevance of the book. In fact, in this book Lispector was able to transgress radically Brazilian prose in the 20th century

Este projeto de pesquisa tem por premissa maior realizar uma análise do segundo romance de Clarice Lispector, O lustre, publicado em 1946 e considerado pela crítica literária e as pesquisas acadêmicas, até o momento, como uma das obras menores da escritora. O estudo analisa a construção do narrador e da personagem principal Virgínia, articulados como as categorias narrativas de maior expressividade e ruptura dentro da história. A pesquisa também objetiva evidenciar as marcas de estéticas vanguardistas e modernas, sobretudo do Impressionismo, que reverberam na escritura de Lispector nesse livro. Todo esse percurso investigativo visa firmar O lustre como obra de grande qualidade estético-literária, desmistificando a opinião crítica sobre a menor relevância dessa narrativa, consolidando-o, deste modo, como um dos primeiros romances em que Clarice Lispector conseguiu com maestria transgredir e ampliar os horizontes da prosa brasileira do século XX
Keywords: Lispector, Clarice 1920-1977; Literatura brasileira - Sec. XX; Impressionismo; Prosa brasileira; Impressionism